Correction: Black bean protein concentrate ameliorates hepatic steatosis by decreasing lipogenesis and increasing fatty acid oxidation in rats fed a high fat-sucrose diet. Issue 1 (8th December 2020) - Hernandez-Velazquez, Irma; Sanchez-Tapia, Monica; Ordaz-Nava, Guillermo; Torres, Nimbe; Tovar, Armando R.; Galvez, Amanda
Abstract : Correction for 'Black bean protein concentrate ameliorates hepatic steatosis by decreasing lipogenesis and increasing fatty acid oxidation in rats fed a high fat-sucrose diet' by Irma Hernandez-Velazquez et al., Food Funct., 2020, DOI: ; 10.1039/d0fo02258f .